Methodology And Theoretical Basis of Teaching Movements - D. Achilova; K. B. Khakimdjanova (Euro Asian Journal Publishing, 2024)
In this article, it is described about movement games and physical exercises, movement games during field trips, working with children individually, children's independent movement activities and recreation.
Keywords: action games; walk; excursion; physical activities